Outcome measurement instruments in Rett syndrome: A systematic review - Romero-Galisteo, Rita Pilar; González-Sánchez, Manuel; Costa, Lara; Brandao, Rita; Ramalhete, Catia; Leao, Carla; Jacobsohn, Lia (Elsevier, 2022)
Objective The aim of the study was to identify and characterize outcome measures for objective and subjective assessment in persons with Rett syndrome (RS). Methods A systematic review was conducted consulting the EBSCO, Cochrane, Web of Science, Scielo, MEDLINE and PsycINFO databases for published studies describing the use of patient-reported outcome measures (PROMs) and other outcome measures in persons with RS. Validation studies and observational studies were included. The PROMs were first described, and then the measurement properties were evaluated using predefined criteria according to the COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN). The outcome measures were then grouped according to the International Classification of Functioning, Disability and Health (ICF) to establish a relationship between outcome measures and ICF domains. Results Twenty out of 2327 articles were appraised, and seventeen different outcome measures were identified and described. Ten outcome measures corresponded to evaluation questionnaires, while the remaining seven assessed functional outcomes: walking distance, physical activity level and ability to interact visually. A relation between these outcome measures that assess RS and the ICF allows understanding that most of the instruments (fifteen) include the assessment of activity limitations. Conclusions The findings of this study seem to be promising for their use by clinicians and researchers, although they have methodological limitations. The accuracy and quality of these individual outcome measures should continue to be assessed in an attempt to gather a consensus on the best tools used in RS.
Keywords: Rett, Síndrome de; Rett syndrome; COSMIN; Systematic Review; outcome measure; psychometric properties